DINAMIKA KEHIDUPAN SOSIAL EKONOMI PETANI KARET BUKIT SARANA KECAMATAN RAO KABUPATEN PASAMAN TAHUN 1996-2020 - Roni Jasmanda; Azmi Fitrisia (Jurnal Kronologi, 2021)
The hill rubber plantation is the first rubber plantation in the Rao Nagari Taruang-Taruang district, Pasaman regency. The hil rubber plantation at this facility was estaplished in 1996. This plantation is the only source of livehood for the local farmers. Which after it was founded in 1996, this rubber plantation has an impact on the sosio- economy of the community. By making a living as a rubber farmer, the community can fulfil their daily needs. Rubber farmers work from morning to evening. Rubber tapping starts from 6 am to 11 pm, if we look at it from the point of view of their daily lives as rubber farmers, they can buy motor bikes, renovate houses, and send their children to school as hingh as possible. After the existence of the hill rubber plantation, this facility had a lot of impact on other areas which later made rubber plantations such as the hill rubber plantions. Keywords: The socio-economic development of the hill rust plantations.